Efektivitas Model Discovery Learning Berbantuan Lingkungan Sekitar dalam Meningkatkan Hasil Belajar IPA Biologi Materi Tumbuhan dan Fungsinya pada Siswa Kelas 3 MI Al Barokah Jember - Silvi Nur Dina; Muhammad Suwignyo Prayogo; Siti Aisyah Putri Andiyani; Isna Maulida (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to assess the effectiveness of the Discovery Learning model that utilizes the surrounding environment in improving the learning outcomes of Biology Science on plant material and its functions in grade 3 students of MI Al Barokah Jember. This approach refers to David A. Kolb's experiential learning theory and Jean Piaget and Lev Vygotsky's constructivism theory, which emphasizes the importance of active student involvement through real-life experiences and social interactions. This study uses a Classroom Action Research (CAR) model with four stages: planning, implementation, observation, and reflection. The research subjects were 24 students, with data obtained through observation, learning outcome tests (pre-test and post-test), and reflective interviews. Data analysis was carried out using quantitative and qualitative descriptive methods. The results showed a significant increase in students' conceptual understanding, with an average pre-test score of 60 increasing to 82 in the post-test, and 83% of students showed improved learning outcomes. Student activity also increased, with more students actively involved in observations, discussions, and presentations. As many as 80–85% of students were able to explain the functions of plant parts based on direct observation. Students responded positively to this lesson, but there were limitations in the variety of plants and the timeframe. It is recommended to reinforce initial understanding with visual aids and allow more time for group discussions.